Hubungan Antara Adversity Quotient Dan Career Adaptability Pada Mahasiswa Tingkat Akhir Prodi Psikologi Islam Iain Batusangkar - Salsabila, Dhea; Desmita, Desmita; Irman, Irman; Sisrazeni, Sisrazeni (Batanang : Jurnal Psikologi, 2022)
The problem in this study is the final year students of Islamic Psychology are havenÔÇÖt a career plan for the future, still donÔÇÖt know their potential and sometimes when they are facing a difficulities or obstacles, they become unfocused and uneasy in doing their activities. This study aims to determine how the relationship between adversity quotient and career adaptability in final year students of Islamic Psychology IAIN Batusangkar. The population and sample of this study were all final year students of Islamic Psychology study program IAIN Batusangkar, totaling 34 people. The data collection technique in this study used the Career Adapt-Ability Scale (CAAS) questionnaire which had been adapted and modified by the Adversity Response Profile questionnaire. The results showed that the significance value was 0.287, with a value of r calculated (0.188) which means there is no significant relationship between adversity quotient and career adaptability in final year students of Islamic Psychology Study Program IAIN Batusangkar with the sign on the result is positive which means the higher the adversity quotient final year students, the higher their career adaptability will be.Keywords: adversity quotient, career adaptability, final year students